Clive Holland (1946-2000) - Barr, William (ARCTIC, 2001)
Clive Holland, archivist, polar historian, and polar encyclopedist, died in Cambridge on 15 September 2000 after a lengthy illness. Clive joined the staff of the Scott Polar Research Institute as historical research assistant in 1968, and by 1975 was filling the roles of archivist, deputy librarian, and museum curator, all three of which posts he held for a decade until his resignation to pursue his polar historical interests full-time. Clive (in collaboration with Dr. Alan Cooke) produced one of the three monumental compendia that really represent his life's work. This was The Exploration of Northern Canada, 500 to 1920: A Chronology, published in 1978. Over the years, this work has been a godsend to Arctic historians working in the Canadian Arctic. Four years later, . Clive published his Manuscripts in the Scott Polar Research Institute, Cambridge, England: A Catalogue. This catalogue is an essential tool for any polar historian, quite apart from its crucial role in the use of the Scott Polar Research Institute collection. Clive's third magnum opus, namely his Arctic Exploration and Development, c. 500 B.C. to 1915: An Encyclopedia, published in 1994, outshines the earlier two. This volume, which uses the same format and system as the earlier Chronology, expands on the latter to embrace the entire circumpolar Arctic. Although in his later years Clive became withdrawn from the polar academic community, he will not be forgotten. His three polar compendia are unlikely to be superseded soon - if ever.